Pengaruh Globalisasi Ekonomi terhadap Peraturan Perundang-Undangan dalam Bidang Sumber Daya Alam di Indonesia - Trias Palupi Kurnianingrum (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2010)
The economic globalization has influenced natural resources legislation. It happens because the basic values of neo economic-liberalism has slipped into the current of globalization, which causing the natural resources legislation can be cancelled by the constitutional court because is not incompatible with the spirit nationalism of our nation. This is what truly happended in Indonesia if an economic constitutional policy is controlled by the constitution of 1945, so the impact is our constitutional wont allow the market mechanism walking freely without a state interference. To overcome this situation, the constitution must collaborate with market mechanism.